Heat treatment and quenching media effects on the thermodynamical, thermoelastical and structural characteristics of a new Cu-based quaternary shape memory alloy - Canbay, Canan Aksu; Karaduman, Oktay; Unlu, Nihan; Baiz, Sivar Aziz; Ozkul, Iskender (Elsevier Sci Ltd, 2019)
In this study, Cu-based shape memory alloy (a smart material) with a new quaternary Cu-22.78Al-2.59Fe-2.44Mn (at%) composition was produced by arc melting and the samples cut from this cast-ingot alloy were homogenized at 900 degrees C for 1 h and quenched in traditional iced-brine water. Then except keeping one as the reference the others were all heat-treated (aged) at 200 degrees C for 1 h and then quenched/cooled in several different media. To find out the effects of the aging and varied quenching/cooling media types on the characteristic martensitic transformation temperatures, thermodynamical parameters and structural properties of this CuAlFeMn shape memory alloy (SMA) the thermal and X-ray measurements were carried out. The differential scanning calorimetry (DSC) and differential thermal analysis (DTA) measurements were made at different heating/cooling rates for all of the different types of the alloy samples. Thermal results showed that the characteristic forward martensite to austenite and backward phase transitions occurred at varied temperatures in between 44 and 176 degrees C and the different samples had different characteristic transformation temperatures and hysteresis due to the different quenching media effects. All of the samples exhibited high temperature shape memory alloy (HTSMA) behavior since all of their austenite start temperatures came up over 100 degrees C. The highest average austenite phase finish temperature belonged to the sample quenched in boiling water and the lowest belonged to the sample quenched in liquid nitrogen. The least amount of transformation entalphy and entropy change values were found for the aged sample quenched in liquid nitrogen which is the fastest coolant medium among others and caused the neatest martensite and interface formations and this was also understood from this sample having the lowest Gibbs free energy difference (Delta G). The X-ray analyses of the CuAlFeMn SMA samples showed the formations of beta 1'(M18R) and gamma 1'(2H) in the alloy and a main peak plane change occurred by aging. Besides this, there has been an adverse magnitude ranking correspondency found between average crystallite size and entropy change values of the aged samples. The analyses showed that the characteristic thermodynamical, thermoelastical and structural parameters of the CuAlFeMn high temperature shape memory alloy are strongly affected from the conditions of composition, aging temperature and quenching/coolant medium type used and the different combinations of those conditions can lead to their own distinctive genuine consequences.
Keywords: CuAlFeMn HTSMA; Quenching media; Thermal aging; Gibbs energy; Elastic strain energy; Martensite